ANALISA TARIF BUS TRANS KOETARADJA KORIDOR 2A (PUSAT KOTA – BLANG BINTANG) BERDASARKAN BIAYA OPERASI KENDARAAN, ABILITY TO PAY DAN WILLINGNESS TO PAY - Buang Turasno; Renni Anggraini; Yusria Darma (Prodi Magister Teknik Sipil Unsyiah, 2019)
Today, the Province of Aceh has implemented mass transportation in the form of buses to overcome congestion. The Aceh Government through the Aceh Transportation Agency in collaboration with the Ministry of Transportation provides mass transportation services called Trans Koetaradja. The Trans Koetaradja bus, which operates in the capital of Aceh Province, reaches the city of Banda Aceh and the district of Aceh Besar. Trans Kutaradja service has opened five corridors up to 2018 including Corridor 2A Keudah - Blang Bintang. In its management the Government of Aceh provides subsidies so that for the time being the Aceh Government has freed up mass transportation services, but the provision of these subsidies will not last forever but will be phased out. So that the community will be subject to tariffs in using the Trans Koetaradja Bus This study aims to determine the amount of passenger tariffs in terms of BOK and using the ATP and WTP methods. The results of this study are for Corridor 2A for the results of tariffs based on BOK is Rp. 6,000, ATP is Rp. 3,800 (students); Rp. 3,900 (students); Rp. 4,000 (general public) and Rp. 6,000 (elderly / disability) while the rate based on WTP is Rp. 3,600 (students); Rp. 3,700 (students); Rp. 3,200 (general public) and Rp. 6,000 (elderly / disability).